Online Learning Talaqqi Method in Pesantren of Indonesia - Slamet Wahyudi; Dudiyono Dudiyono; Kholid Mawardi (STAI Hubbulwathan Duri, 2023)
A new problem has come since the emergence of the term social distancing. Many parties continue to feel concerned, especially those who care about the future of Pesantren's education. The greatest fear is that there is a lost generation if this problem is not immediately addressed. Pesantren, as a forum for the development of religious knowledge, has a big role in the civilization of life. The formulation of the Islamic education curriculum as a supporter is inspired by primary sources of Islamic teachings. Every learning must use the method to deliver the goals that an educational institution has set. One of the methods used in Pesantren is learning with the Talaqqi method. This study aimed to discuss further how the Talaqqi method was implemented in Pesantren during the Covid-19 pandemic. The author gathers information from references to scientific journals, articles, current news, and direct observations in the area of Pesantren. The result showed that this method used in each Pesantren in Indonesia during the current pandemic is very different. The problem with this study is that it only looks at one way to learn. It would be better if future research compared many different ways to learn.